2020
DOI: 10.1111/ane.13214
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of benign recurrent vertigo: A longitudinal study

Abstract: Objective To study the demographics, vertigo profiles, and outcomes of adult patients with benign recurrent vertigo (BRV). Patients and methods This prospective study included patients with BRV who were admitted to a tertiary neurology clinic between June 2013 and June 2017. All patients underwent detailed clinical interviews and related examinations. A follow‐up was then conducted through an outpatient or telephone interview. Results A total of 66 patients (48 females) were enrolled, and the mean age at the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…Similar rates of accompanying auditory symptoms (3-14%) have been reported for BRV patients without migraine before. Furthermore, the relative frequencies of photophobia or phonophobia (5.7% each) and non-migrainous headache (14%) in our study were similar to values from the literature (13,16,17,23).…”
Section: Accompanying Symptomssupporting
confidence: 90%
See 3 more Smart Citations
“…Similar rates of accompanying auditory symptoms (3-14%) have been reported for BRV patients without migraine before. Furthermore, the relative frequencies of photophobia or phonophobia (5.7% each) and non-migrainous headache (14%) in our study were similar to values from the literature (13,16,17,23).…”
Section: Accompanying Symptomssupporting
confidence: 90%
“…The vestibular syndrome of RVS-NOS seems to be stable over time rather than a transitory condition converting into another vertigo syndrome. Previous studies reported that the diagnosis of patients with BRV/RV had to be changed to migraine in only 2 to 7.5% of cases and to MD in only 1 to 4% over median follow-up times between 31 and 63 months (12,17,29). This is in line with the results from our study where the mean duration of the vestibular syndrome before the patients' first visit in a neurotology clinic was not significantly different between patients with RVS-NOS (5.40 ± 6.10 years) as compared to VM (5.26 ± 6.59 years) or MD (7.63 ± 8.09 years) indicating a rather stable vestibular syndrome not changing over the years.…”
Section: Rationale Of the Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We are very grateful for Dr van Leeuwen's valuable comment on our article. 1 Recurrent vertigo is common in clinical work. As early as 1979, Slater firstly used benign recurrent vertigo (BRV) to describe that some adult patients present with recurrent vertigo without neurologic or any auditory symptoms.…”
Section: Reply To: "Clinical Features and Outcomes Of Benign Recurrenmentioning
confidence: 99%